DAMPAK LINGKUNGAN KERJA NON-FISIK DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Bernadeth Tongli; Bartholomeus Tandiayu; Johanis Panggeso; Charles Wijaya Wong (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
Various types of research have been conducted on the environment and compensation in relation to employee performance, but specifically non-physical environmental impacts and compensation in state-owned enterprises are still rarely found online journals in relation to employee performance. This study aims to investigate the impact of the non-physical work environment and compensation on employee performance. Simple random sampling technique is used to select population members from employees of PT. Telkom Regional VII Makassar City. This research is an associative type of research with data collection methods through surveys. Data analysis uses multiple linear regression analysis. The results showed that the non-physical environment did not have a significant and positive effect on employee performance. Meanwhile compensation affects the performance of employees The coefficient of determination shows that the non-physical work environment and Compensation can shape the direction of employee performance by 24.9%, while 75.1% is determined by other variables not included in this research model.